INTERNATIONAL FINANCIAL REPORTING STANDARDS AND THEIR IMPORTANCE (Ustozlar uchun, 2026)
This article analyzes the International Financial Reporting Standards (IFRS) and their significance in the modern economy. The paper examines the origin of IFRS, its main principles, role in the global economy, and benefits for effective corporate financial management. The study also discusses the advantages and challenges of implementing IFRS, as well as the transparency and comparability of financial information. The results indicate that IFRS provides reliable, accurate, and transparent financial data for companies and investors and plays a key role in global financial integration.